2009
DOI: 10.1590/s1413-86702009000300013
|View full text |Cite
|
Sign up to set email alerts
|

Reference range for T lymphocytes populations in blood donors from two different regions in Brazil

Abstract: This study defined the normal variation range for different subsets of T-lymphocyte cells count in two different Brazilian regions. We analysed the T-lymphocytes subpopulations (CD3+, CD4+, CD8+) in blood donors of two Brazilian cities, located in North (Belem, capital state of Para, indian background) and Northeast (Salvador, capital state od Bahia, African background) regions of Brazil. Results were compared according to gender, stress level (sleep time lower than 8 hours/day), smoking, and alcohol intake. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
4
17
2
Order By: Relevance
“…Moreover, relative and absolute values for T CD4+ count were higher in females and these findings were consistent with previous studies [3,6,7,14,16,17,19,22,23]. Maini and colleagues suggested that hormonal differences between genders might explain this difference in T CD4+ counts [15].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, relative and absolute values for T CD4+ count were higher in females and these findings were consistent with previous studies [3,6,7,14,16,17,19,22,23]. Maini and colleagues suggested that hormonal differences between genders might explain this difference in T CD4+ counts [15].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, gender comparison showed differences only for T CD8+ absolute count, for which female had higher values, similarly to those reported in adults in the northern rural region of Tanzania [16]. Comparing the results of this study (Table 1) with those by Torres et al [23] showed differences in T CD8+ reference ranges for healthy Brazilian people.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations